The Covid generation: Identifying risks and protective factors for young people's pathways through the Covid-19 pandemic in Switzerland [CovidGen] - (:unkn) unknown (My University, 2025)
The Covid Generation is a three-year project (2023-2026), funded by the SNFS through the NRP80 “Covid-19 in Society”. This collaborative project involves researchers from FORS, the University of Lausanne and the University of Neuchâtel. The project is also conducted in close collaboration with several partners from the policy field. We examine wellbeing of young people as well as the response of the policy field to support their wellbeing during the COVID-19 pandemic. The project examines wellbeing of young people as well as the response of the policy field to support their wellbeing during the COVID-19 pandemic. The project will answer the following two main questions: 1. How has the COVID-19 pandemic affected wellbeing of young people? Specifically, we examime how wellbeing changed over time, what were the main drivers, which groups were most at risk and which protective factors mitigated negative consequences for wellbeing? 2. What can we learn from the policy response for future crises? Specifically, we examine whether and how did policy initiatives to support young people during the pandemic focus on the groups most at risk, and what lessons can be drawn from the development and implementation of these programs?
Keywords: Wellbeing; mental health; Youth; Social policy